Application of probiotic microcapsules Bacillus cereus BR2 with different doses for the prevention of Aeromonas hydrophila NFC1 infection in catfish Clarias sp. - Faoziyatunnisa, Nurul; Yuhana, Munti; Wahjuningrum, Dinamella; Nuryati, Sri; Afiff, Usamah (Jurnal Akuakultur Indonesia, 2024)
This study aims to analyze the administration of microencapsulated probiotic Bacillus cereus BR2 through feed atdifferent doses on the survival, immune response, and digestive enzyme activity of catfish Clarias sp. infected with Aeromonas hydrophila NFC1. The research design consisted of five treatments and three replications: (K-) feeding without the supplementation of probiotics fish injected with Phosphate-buffered saline solution; (K+) feeding without the supplementation of probiotics, fish injected with A. hydrophila NFC1 cell suspension (106 CFU/mL); (P1) feeding with supplementation of B. cereus BR2 microcapsules at a dose of 0.5% (w/w); (P2) feeding with the supplementation of B. cereus BR2 microcapsules at a dose of 1% (w/w; (P3) feeding with the supplementation of B. cereus BR2 microcapsules at a dose of 2% (w/w). All treatments of P1, P2, and P3 were intramuscularly injected with A. hydrophila NFC1 cell suspension. Catfish in average body weight of 3.73 ± 0.22 g were reared in tanks filled with 30 liters of water, at a density of 15 fish per container. A feed supplementation trial was performed for 40 days with feeding times three times a day; and a 5% feeding rate reevaluated based on biomass. Fish rearing was continued after the challenge test with A. hydrophila NFC1 for 10 days. The results showed that the application of supplemented feed containing B. cereus BR2 probiotic microcapsules increased the survival rate, immune response, and digestive enzyme activities of catfish which was infected with A. hydrophila NFC1, 2% microcapsule supplementation demonstrated the best result. Keywords: Aeromonas hydrophila NFC1, Bacillus cereus BR2, catfish, microcapsule, probiotics ABSTRAK Penelitian ini bertujuan untuk menganalisis pemberian mikrokapsul probiotik Bacillus cereus BR2 melalui pakan dengan dosis berbeda terhadap sintasan, respons imun, dan aktivitas enzim pencernaan ikan lele Clarias sp. yang diinfeksi Aeromonas hydrophila NFC1. Rancangan penelitian yang digunakan terdiri dari lima perlakuan dan tiga ulangan, yaitu (K-) pemberian pakan tanpa suplementasi probiotik dan diinjeksi PBS; (K+) pemberian pakan tanpa suplementasi probiotik dan diinfeksi A. hydrophila NFC1; (P1) pemberian pakan dengan suplementasi mikrokapsul B. cereus BR2 dosis 0,5% (b/b); (P2) pemberian pakan dengan suplementasi mikrokapsul B. cereus BR2 dosis 1%; (P3) pemberian pakan dengan suplementasi mikrokapsul B. cereus BR2 dosis 2%, masing-masing diinfeksi A. hydrophila NFC1. Benih lele dengan ukuran bobot rata-rata sekitar 3.73 ± 0.22 g dipelihara di dalam akuarium bervolume 30 L dengan kepadatan 15 ekor per wadah selama 40 hari, dengan pemberian pakan bersuplemen sebanyak tiga kali sehari, dengan 5% pemberian pakan yang dievaluasi berdasarkan bobot biomassa. Pemeliharaan ikan dilanjutkan setelah uji tantang dengan A. hydrophila NFC1 (106 CFU/mL) yang dilakukan hingga 10 hari pasca injeksi. Hasil penelitian menunjukkan aplikasi mikrokapsul probiotik B. cereus BR2 melalui pakan mampu meningkatkan sintasan, respons imun, dan aktivitas enzim pencernaan ikan lele yang diinfeksi A. hydrophila NFC1, dengan suplementasi mikrokapsul 2% sebagai hasil terbaik. Kata kunci: Aeromonas hydrophila NFC1, Bacillus cereus BR2, ikan lele, mikrokapsul, probiotik